Processing of CaLa2S4 infrared transparent ceramics: A comparative study of HP and FAST/SPS techniques. Issue 4 (2nd December 2019) - Durand, Guillaume R.; Bizot, Quentin; Herbert, Nathalie; Quéméré, Samuel; Pasturel, Mathieu; Zhang, Xiang‐Hua; Merdrignac‐Conanec, Odile
Abstract: The densification of CaLa2 S4 (CLS) powders prepared by combustion method was investigated by the use of Field‐Assisted Sintering Technique (FAST) and Hot Pressing (HP). CLS powders were sintered using FAST at 1000°C at different pressures and heating rates and sintered by HP under 120 MPa from 800°C to 1100°C for 6 hours with a heating rate of 10°C/min. Comparison of both techniques was further realized by use of the same conditions of pressure, dwell time, and heating rate. Complementary techniques (XRD, SEM‐EDS, density measurements, FTIR spectroscopy) were employed to correlate the sintering processes/parameters to the microstructural/compositional developments and optical transmission of the ceramics. Both sintering techniques produce ceramics with submicrometer grain size and relative density of about 99%. Nevertheless, HP is more suitable to densify CLS ceramics without fragmentation and also reach higher transmission than FAST. Transmission of 40%–45% was measured out of a possible maximum of 69% based on the Fresnel losses in the 8‐14 μm window when HP is applied at 1000°C for 6 hours under 120 MPa. In both techniques, ceramics undergo reduction issues that originate from graphitic sintering atmosphere.